Intelligent data engineering and automated learning -- IDEAL 2018. 19th International Conference, Madrid, Spain, November 21-23, 2018, Proceedings /: 19th International Conference, Madrid, Spain, November 21-23, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available